Comprehensive proteomic analysis of the wheat pathogenic fungus Zymoseptoria tritici. Issue 1 (24th November 2015) - Yang, Fen; Yin, Qi
Abstract : Zymoseptoria tritici causes Septoria tritici blotch disease of wheat. To obtain a comprehensive protein dataset of this fungal pathogen, proteomes of Z. tritici growing in nutrient‐limiting and rich media and in vivo at a late stage of wheat infection were fractionated by 1D gel or strong cation exchange (SCX) chromatography and analyzed by LC‐MS/MS. A total of 5731, 5376 and 3168 Z. tritici proteins were confidently identified from these conditions, respectively. Of these in vitro and in planta proteins, 9 and 11% were predicted to contain signal peptides, respectively. Functional classification analysis revealed the proteins were involved in the various cellular activities. Comparison of three distinct protein expression profiles demonstrates the elevated carbohydrate, lipid and secondary metabolisms, transport, protein processing and energy production specifically in the host environment, in contrast to the enhancement of signaling, defense, replication, transcription and cell division in vitro. The data provide useful targets towards a better understanding of the molecular basis of Z. tritici growth, development, stress response and pathogenicity.